ANALISIS KELAYAKAN ISI BUKU TEKS “MARDIKA BASA LAN SASTRA JAWA” KELAS VII - Nissa Kusuma Wardani; Kenfitria Diah Wijayanti; Budi Waluyo (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2025)
Textbooks are books that serve as guidelines for the teaching and learning process, one of which is the Class VII Javanese language textbook with the title "Mardika Basa lan Sastra Jawa" published by Erlangga. This research aims to describe the suitability of the content in the Class VII Javanese language textbook "Mardika Basa lan Sastra Jawa". This research is qualitative research with the technique used is content analysis, namely using interactive analysis (data collection, data reduction, data presentation, and drawing conclusions). Content feasibility data was analyzed using instruments with relevant theory. The appropriateness of the content is reviewed from the suitability of the material and its accuracy. Based on the results of the analysis obtained, it can be concluded that the appropriateness of the content in the textbook "Mardika Basa lan Sastra Jawa" published by Erlangga obtains a percentage value of 74.4% if it is based on the content standards of the independent curriculum for local Javanese language content lessons, this has meaning that this book is suitable for use as a learning handbook in schools.